A scholarly roundtable with Deep Focus and DIRECTUBE. Issue 2 (2nd September 2021) - Cao, Liuying; Che, Lin; Chen, Timmy Chih-Ting; Chen, Xiaoran; He, Belinda Qian; Jiang, Zoe Meng; Ma, Ran; Shen, Hancheng; Zhao, Jin
Abstract: Co-organized by JCC's guest editors Timmy Chen and Belinda He, a roundtable discussion took place between December 2020 and January 2021. Co-founders of two remarkable cinephilic organizations in the Chinese-speaking world (Deep Focus and DIRECTUBE) and scholars from various backgrounds were invited to share their observations and insights about cinema and cinephilia. Participants from six time zones started with a roundtable gathering via video conferencing and continued the conversation through an online document. The shared file afforded each participant the opportunity to contribute to the discussion at their own convenience, thereby enabling the roundtable to develop organically within the two-month period. The roundtable during the pandemic was a timely attempt to experiment with the notion of roundtable, whereby we appreciate and intend to keep the friction, interruption, fragmental thoughts, in-between moments, and even random diversions in the process. Such a multivocal conversation was a live event among us and remains ongoing for everyone. Part I of the roundtable, as shown below, revolves around participants' positionalities and border-crossing experiences about cinema. In Part II, our special guest, Bérénice Reynaud recounts her cinephiliac experience of working as a non-Chinese, non-Chinese-speaking scholar and curator who has developed a special relationship to Chinese-language cinema.